Chemistry Teachers’s Understanding, Implementation, and Barriers of Education for Sustainable Development (ESD) in South Sulawesi - Sumiati Side; Munawwarah (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
This study aims to map the understanding, implementation, and supporting or hindering factors of Education for Sustainable Development (ESD) in chemistry education among senior high school teachers. A descriptive quantitative approach supported by qualitative analysis was employed. Data were collected from 13 chemistry teachers across five regency in South Sulawesi through an online questionnaire (Google Form). The instrument consisted of three main Likert-scale sections (understanding, implementation, and supporting/hindering factors) and four open-ended questions. Data were analyzed by calculating indices (0–100) and conducting a gap analysis between understanding and implementation, complemented by simple thematic coding of open responses. The results indicate that teachers’ understanding of ESD is relatively high (76.4), whereas implementation (62.7) and supporting/hindering factors (61.5) remain at a medium–high level. The gap analysis revealed that most teachers fall into the Understanding > Implementation category, suggesting that their conceptual knowledge surpasses classroom practices. Key barriers include limited laboratory facilities, insufficient teaching resources, time constraints, and low student literacy. Qualitative findings further reinforced these results, showing that teachers acknowledged the importance of ESD for raising environmental and social awareness but admitted difficulties in applying it. Suggested improvements included continuous teacher training, provision of ESD-based learning resources, and stronger school-level policies. These findings highlight the urgent need for systematic interventions such as professional development, adequate resources, and supportive educational policies to enhance the implementation of ESD in chemistry education.